Bi2S3 composite PbBiO2Cl catalyst as well as preparation method and application thereof

Through the development of Bi2S3 composite PbBiO2Cl catalyst, the synergistic effect under light and ultrasonic vibration is used to solve the problem that the photocatalyst performance is limited by material characteristics, and the efficient degradation effect of organic pollutants is achieved, showing the water purification Wide application potential.

CN119158600APending Publication Date: 2024-12-20ZHEJIANG NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411452509.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The performance improvement of existing photocatalysts is limited by the material's own characteristics, and it is difficult to effectively utilize a variety of external fields to improve photocatalytic efficiency.

Method used

A Bi2S3 composite PbBiO2Cl catalyst was developed, and a nanoscale Bi2S3 was deposited on PbBiO2Cl nanosheets to form a type I heterojunction structure, combining light and ultrasonic vibration driving, and using photothermal and piezoelectric effects to synergistically improve catalytic activity.

Benefits of technology

It significantly improves photocatalytic activity and piezoelectric catalytic efficiency, and can efficiently degrade organic pollutants under light and ultrasonic vibration, and catalysts show wide application prospects in water purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158600A_ABST
    Figure CN119158600A_ABST
Patent Text Reader

Abstract

The invention discloses a Bi2S3 composite PbBiO2Cl catalyst and a preparation method and application thereof, and belongs to the technical field of catalysts.The Bi2S3 composite PbBiO2Cl catalyst is characterized in that Bi2S3 nanoparticles are deposited on the surface of a PbBiO2Cl nanosheet, the photocatalytic and piezoelectric catalytic performance of PbBiO2Cl is promoted through the capture effect of Bi2S3 on electrons, and Bi2S3 can capture electrons to promote separation of carriers. Meanwhile, the band gap of Bi2S3 is narrower (1.3-1.7 eV), and electrons of Bi2S3 are easy to interact with crystal lattices through a non-radiation process, so that heat energy is generated; meanwhile, a local plasmon resonance effect can be generated, absorption of the material to light is enhanced through the effect, and light energy is rapidly converted into local heat energy, so that Bi2S3 shows an excellent photothermal effect and can activate organic pollutants and accelerate a photocatalytic reaction; and after the compound is compounded with PbBiO2Cl, the catalytic effect is greatly improved under the catalytic conditions of piezoelectricity and light-piezoelectricity synergistic interaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts and organic degradation, and in particular to a Bi 2 S 3 Composite PbBiO 2 Cl catalyst and its preparation method and application. Background Art

[0002] With the rapid growth of population and the acceleration of industrialization, environmental pollution is becoming increasingly serious and has become a major obstacle to the sustainable development of human society. Traditional pollution control methods mainly remove pollutants through biological, physical or chemical processes, but these methods have certain limitations. In contrast, photocatalytic technology uses clean and renewable solar energy to achieve reactions such as pollutant degradation and hydrogen production under mild conditions, and is considered to be an ideal way to solve environmental pollution and energy problems. The research and development of efficient photocatalytic materials is the key to the development of photocatalytic technology. However, the current design of photocatalysts mainly improves performance by modifying the internal structure of the material, but this method is limited by the characteristics of the material itself. In contrast, external field coupling technology provides more possibilities for performance improvement.

[0003] When external fields such as heat, electricity, magnetism, microwaves, and ultrasound are introduced, the corresponding energy can be transferred to the photocatalytic system, activating pollutant molecules and promoting the separation of photogenerated carriers, thereby significantly improving the photocatalytic efficiency. The photothermal effect refers to the absorption of red light or near-infrared light by the catalyst, converting light energy into heat energy, causing the local temperature of the catalyst to rise, thereby activating the reactant molecules and accelerating the photocatalytic reaction process. The ultrasonic field enhances the photocatalytic performance through the piezoelectric effect of the catalyst. The cavitation effect of ultrasound produces a strong shock wave, which causes the catalyst to deform and stimulates the piezoelectric effect to form a piezoelectric field. This piezoelectric field can not only induce piezoelectric catalytic reactions, but also promote the separation of photogenerated carriers, thereby significantly improving the photocatalytic efficiency. The research and development of this type of catalytic material that can utilize a variety of energy fields is expected to promote the great development of photocatalytic technology.

[0004] To achieve efficient utilization of multiple energy fields, the selection and design of catalytic materials are key. 2 X is a layered Bi-based compound with staggered [PbBiO 2 ] plates and double [X] sheets. Its layered structure gives PbBiO 2 The internal electric field of X enables the electron-hole pairs to be effectively separated, thus showing good photocatalytic activity. 2 ] and [I] plates, the weak non-bonded forces (van der Waals forces) between them make PbBiO 2 X can easily form ultrathin two-dimensional structures (nanoplates) that exhibit piezoelectric properties. 2X-nanosheets are a promising material that possesses both photocatalytic and piezoelectric catalytic properties and can purify water using light and ultrasonic vibrations. Summary of the invention

[0005] The object of the present invention is to provide a Bi 2 S 3 Composite PbBiO 2 Cl catalyst; Another object of the present invention is to provide a Bi 2 S 3 Composite PbBiO 2 A method for preparing a catalyst for BiCl; Another object of the present invention is to provide a 2 S 3 Composite PbBiO 2 Application of Cl catalysts.

[0006] The present invention provides a Bi 2 S 3 Composite PbBiO 2 Catalyst of Cl, nano-Bi 2 S 3 Deposited on PbBiO 2 Cl nanosheets, Bi in the composite catalyst 2 S 3 With PbBiO 2 The molar ratio of Cl is x%, where 1≤x≤8.

[0007] Furthermore, Bi 2 S 3 With PbBiO 2 The molar ratio of Cl is 4%.

[0008] Bi 2 S 3 When the addition amount is within this range, the catalytic effect is best.

[0009] Furthermore, Bi 2 S 3 With PbBiO 2 Cl forms a type I heterojunction structure.

[0010] Bi 2 S 3 With PbBiO 2 Cl forms a type I heterojunction structure, which effectively promotes the separation of photogenerated carriers and thus improves the overall photocatalytic activity.

[0011] The present invention also provides a Bi 2 S 3 Composite PbBiO 2The preparation method of the catalyst of Cl comprises the following steps:

[0012] S1 synthesis of PbBiO 2 Cl: Disperse bismuth nitrate, lead acetate and sodium chloride in water and mix them evenly to form a solution; add sodium hydroxide to adjust the pH of the solution to 11; perform hydrothermal reaction at 170-185°C for 20-28h, cool to room temperature, separate the reaction solution into solid and liquid, wash and dry to obtain PbBiO 2 Cl;

[0013] S2 Deposition Bi 2 S 3 :The obtained PbBiO 2 Cl is dispersed in water, sodium sulfide is added, and mixed evenly; bismuth nitrate is added, and mixed evenly; hydrothermal reaction is carried out at 110-130° C. for 14-18 hours, cooled to room temperature, solid-liquid separation of the reaction liquid is carried out, washing, and drying to obtain Bi as described in any one of claims 1-3 2 S 3 Composite PbBiO 2 The catalyst of Cl.

[0014] Hydrothermal reaction is a chemical reaction carried out under high temperature and high pressure conditions, usually in a closed reactor (such as an autoclave). This reaction method uses water as a solvent to promote the dissolution, crystallization, decomposition or synthesis of substances under high temperature and high pressure.

[0015] The Bi disclosed in the present invention 2 S 3 Composite PbBiO 2 The Cl catalyst is prepared by a simple two-step hydrothermal reaction, and the preparation process is simple, easy to operate, and suitable for large-scale production.

[0016] Furthermore, in step S1, the molar ratio of bismuth nitrate, lead acetate and sodium chloride is 1:1:1.

[0017] Furthermore, in step S1, the volume ratio of the mole of bismuth nitrate to the solution in the hydrothermal reaction is (2.9-3.1) mmol:80 mL.

[0018] Furthermore, in step S2, the molar ratio of sodium sulfide to bismuth nitrate is (3.5-4.5):2; in the hydrothermal reaction, PbBiO 2 The molar ratio of Cl to the volume ratio of the system is 1mmol:8L.

[0019] The present invention also provides a Bi 2 S 3 Composite PbBiO 2 The application of the catalyst of Cl, Bi obtained by the preparation method described above 2 S3 Composite PbBiO 2 The Cl catalyst is added to the liquid containing the pollutants to be treated, and light and ultrasound are used to degrade the pollutants.

[0020] Bi 2 S 3 Composite PbBiO 2 Cl catalysts exhibited the synergistic effect of photocatalysis and piezoelectric catalysis. Under the combined action of light and ultrasound, the degradation efficiency of organic pollutants was increased by 1-4 times. 2 The piezoelectric effect of Cl was realized, which effectively promoted the degradation reaction.

[0021] Bi 2 S 3 With PbBiO 2 Cl forms a type I heterojunction structure, which effectively promotes the separation of photogenerated carriers. 2 S 3 The photothermal effect further enhances the activation of organic pollutants. 2 S 3 Composite PbBiO 2 Cl catalysts have broad application prospects in water purification.

[0022] Furthermore, Bi 2 S 3 Composite PbBiO 2 The ratio of the mass of the Cl catalyst to the volume of the liquid to be treated is 0.8-1.2 g / L; the power of the ultrasonic generator is 100-140 W.

[0023] Furthermore, the illumination uses a xenon lamp to degrade pollutants; the power of the xenon lamp is 300-400W.

[0024] The present invention provides a Bi 2 S 3 Composite PbBiO 2 Cl catalyst, in PbBiO 2 Surface deposition of BiCl nanosheets 2 S 3 Nanoparticles, through Bi 2 S 3 The electron capture effect promotes the 2 Photocatalytic and piezocatalytic properties of Cl,Bi 2 S 3 It can capture electrons and promote the separation of carriers. 2 S 3The band gap of Bi is narrow (1.3-1.7eV), and its electrons can easily interact with the lattice through non-radiative processes, thereby generating heat energy; at the same time, it can also produce a localized plasmon resonance effect, which enhances the material's absorption of light and quickly converts light energy into local heat energy. Therefore, Bi 2 S 3 It exhibits excellent photothermal effect, can activate organic pollutants and accelerate photocatalytic reactions; 2 After Cl complexation, the catalytic effect is greatly increased under the catalytic conditions of piezoelectric and photo-piezoelectric synergistic enhancement. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The X-ray powder diffraction (XRD) spectra of Example 3 and Comparative Examples 1-2 of the present invention;

[0026] Figure 2 X-ray photoelectron spectroscopy (XPS) of Example 3 and Comparative Examples 1-2 of the present invention;

[0027] Figure 3 Transmission electron microscope (TEM) images of Example 3 and Comparative Example 1 of the present invention;

[0028] Figure 4 The UV-visible diffuse reflectance spectra (DRS) of Example 3 and Comparative Examples 1-2 of the present invention;

[0029] Figure 5 The results of piezoelectric catalytic degradation of RhB in Examples 1-5 and Comparative Examples 1-2 of the present invention are shown;

[0030] Figure 6 It is the first-order kinetic fitting diagram of the piezoelectric catalytic degradation of RhB in Examples 1-5 and Comparative Examples 1-2 of the present invention;

[0031] Figure 7 This is a graph showing the results of the piezoelectric catalytic degradation of RhB cycle test in Example 3 of the present invention;

[0032] Figure 8 This is a diagram showing the results of degradation of RhB by piezoelectric catalysis, photocatalysis and photo-piezoelectric synergistic catalysis in Example 3 of the present invention;

[0033] Fig. 9 This is a first-order kinetic fitting diagram of the degradation of RhB by piezoelectric catalysis, photocatalysis and photo-piezoelectric synergistic catalysis in Example 3 of the present invention;

[0034] Fig.10 The electrochemical impedance spectroscopy (ESI) of Example 3 and Comparative Examples 1-2 of the present invention;

[0035] Fig.11This is a graph showing the results of piezoelectric catalytic degradation of different pollutants within 90 minutes in Example 3 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0037] Example 1

[0038] Preparation of Bi 2 S 3 Composite PbBiO 2 Cl catalyst:

[0039] (1) Use an electronic analytical balance to accurately weigh 1.4552 g (0.003 mol) of bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2 O), 1.1370 g (0.003 mol) lead acetate trihydrate (C 4 H 6 O 4 Pb·3H 2 O) and 0.0.17532 g (0.003 mol) of sodium chloride (NaCl), dispersed them in 60 mL of deionized water, and magnetically stirred for 0.5 hours. After the stirring was completed, 1 mol / L sodium hydroxide solution was slowly added dropwise under continuous stirring to adjust the pH value of the solution to 11, and stirring was continued for 30 minutes. Subsequently, the above suspension was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, ultrapure water was added to make the total volume of the suspension reach 80 mL, and a hydrothermal reaction was carried out at 180 ° C for 24 hours. After the reaction was completed, it was cooled to room temperature, the supernatant was poured off, and the precipitate was washed and centrifuged three times with a mixed solution of ultrapure water and alcohol. The washed precipitate was placed in an oven and dried at 60 ° C for 12 hours to obtain the target product PbBiO 2 Cl.

[0040] (2) Weigh 0.50 g of synthesized PbBiO 2 Cl powder was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 minutes. Then 0.0198 g of sodium sulfide nonahydrate (Na 2 S·9H 2 O) was added to the above solution, stirred for 10 minutes, and then 0.010 g of bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2O). Continue magnetic stirring for 40 minutes. Transfer the above suspension to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, add ultrapure water to make the total volume of the suspension 80mL, and perform hydrothermal reaction at 120°C for 16 hours. Collect the precipitate by centrifuge. Wash with ultrapure water and alcohol three times respectively. Finally, put the precipitate into a vacuum oven and dry it in a vacuum environment at 60°C for 12 hours to obtain the target product Bi 2 S 3 Composite PbBiO 2 Cl catalyst, where Bi 2 S 3 With PbBiO 2 The molar ratio of Cl is 1%.

[0041] Example 2

[0042] Preparation of Bi 2 S 3 Composite PbBiO 2 Cl catalyst:

[0043] (1) The same steps as (1) in Example 1.

[0044] (2) Weigh 0.50 g of synthesized PbBiO 2 Cl powder was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 minutes. Then 0.0595 g of sodium sulfide nonahydrate (Na 2 S.9H 2 O) was added to the above solution, stirred for 10 minutes, and then 0.030 g of bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2 O). Continue magnetic stirring for 40 minutes. Transfer the above suspension to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, add ultrapure water to make the total volume of the suspension 80mL, and perform hydrothermal reaction at 120°C for 16 hours. Collect the precipitate by centrifuge. Wash with ultrapure water and alcohol three times respectively. Finally, put the precipitate into a vacuum oven and dry it in a vacuum environment at 60°C for 12 hours to obtain the target product Bi 2 S 3 Composite PbBiO 2 Cl catalyst, where Bi 2 S 3 With PbBiO 2 The molar ratio of Cl is 3%.

[0045] Example 3

[0046] Preparation of Bi 2 S 3 Composite PbBiO 2Cl catalyst:

[0047] (1) The same steps as (1) in Example 1.

[0048] (2) Weigh 0.50 g of synthesized PbBiO 2 Cl powder was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 minutes. Then 0.0794 g of sodium sulfide nonahydrate (Na 2 S·9H 2 O) was added to the above solution, stirred for 10 minutes, and then 0.0401 g of bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2 O). Continue magnetic stirring for 40 minutes. Transfer the above suspension to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, add ultrapure water to make the total volume of the suspension 80 mL, and perform hydrothermal reaction at 120°C for 16 hours. Collect the precipitate by centrifuge. Wash with ultrapure water and alcohol three times respectively. Finally, put the precipitate into a vacuum oven and dry it in a vacuum environment at 60°C for 12 hours to obtain the target product Bi 2 S 3 Composite PbBiO 2 Cl catalyst, where Bi 2 S 3 With PbBiO 2 The molar ratio of Cl is 4%.

[0049] Example 4

[0050] Preparation of Bi 2 S 3 Composite PbBiO 2 Cl catalyst:

[0051] (1) The same steps as (1) in Example 1.

[0052] (2) Weigh 0.50 g of synthesized PbBiO 2 Cl powder was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 minutes. Then 0.0993 g of sodium sulfide nonahydrate (Na 2 S·9H 2 O) was added to the above solution, stirred for 10 minutes, and then 0.0501 g of bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2O). Continue magnetic stirring for 40 minutes. Transfer the above suspension to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, add ultrapure water to make the total volume of the suspension 80 mL, and perform hydrothermal reaction at 120°C for 16 hours. Collect the precipitate by centrifuge. Wash with ultrapure water and alcohol three times respectively. Finally, put the precipitate into a vacuum oven and dry it in a vacuum environment at 60°C for 12 hours to obtain the target product Bi 2 S 3 Composite PbBiO 2 Cl catalyst, where Bi 2 S 3 With PbBiO 2 The molar ratio of Cl is 5%.

[0053] Example 5

[0054] Preparation of Bi 2 S 3 Composite PbBiO 2 Cl catalyst:

[0055] (1) The same steps as (1) in Example 1.

[0056] (2) Weigh 0.50 g of synthesized PbBiO 2 Cl powder was dispersed in 50 mL of ultrapure water and ultrasonicated for 30 minutes. Then 0.1588 g of sodium sulfide nonahydrate (Na 2 S·9H 2 O) was added to the above solution, stirred for 10 minutes, and then 0.0800 g of bismuth nitrate pentahydrate (Bi(NO 3 ) 3 ·5H 2 O). Continue magnetic stirring for 40 minutes. Transfer the above suspension to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, add ultrapure water to make the total volume of the suspension 80mL, and perform hydrothermal reaction at 120°C for 16 hours. Collect the precipitate by centrifuge. Wash with ultrapure water and alcohol three times respectively. Finally, put the precipitate into a vacuum oven and dry it in a vacuum environment at 60°C for 12 hours to obtain the target product. Bi 2 S 3 Composite PbBiO 2 Cl catalyst, where Bi 2 S 3 With PbBiO 2 The molar ratio of Cl is 8%.

[0057] Comparative Example 1

[0058] Preparation of catalyst PbBiO 2 Cl:

[0059] The same steps as in Example 1 (1) were followed to obtain the target product PbBiO 2 Cl catalyst.

[0060] Comparative Example 2

[0061] Weigh 1.5891g of sodium sulfide nonahydrate and disperse it in 50mL of deionized water and stir for 10 minutes. Subsequently, add 0.8022g of bismuth nitrate pentahydrate and continue stirring for 40 minutes. After that, add deionized water until the total volume reaches 80mL. Transfer the resulting mixture to a stainless steel autoclave with a polytetrafluoroethylene liner and react at 120°C for 16 hours. After the reaction is completed, the product is collected by centrifugation and washed several times with distilled water and ethanol. Finally, the washed product is vacuum dried at 60°C for 8 hours to obtain the target product Bi 2 S 3 .

[0062] Performance testing and results:

[0063] X-ray diffraction (XRD) analysis was performed using a D8 Advance (BRUKER AXS GMBH, Germany) X-ray diffractometer with Cu Kα radiation (40 kV / 40 mA).

[0064] UV-visible diffuse reflectance spectroscopy (DRS) was performed on a UV-visible spectrophotometer (Agilent Cary5000) with BaSO as the reference sample. 4 .

[0065] Transmission electron microscopy (TEM) analysis was performed using a JEM-2010F transmission electron microscope with an accelerating voltage of 200 kV.

[0066] X-ray photoelectron spectroscopy (XPS) analysis was performed using a Thermo Scientific ESCALAB 250Xi microprobe instrument with Al-Kα radiation as the light source.

[0067] The catalysts obtained in Example 3 and Comparative Examples 1-2 were subjected to XRD, XPS, TEM, and DRS tests. The results are as follows: Figure 1-4 shown.

[0068] like Figure 1 As shown, in Example 3, due to Bi 2 S 3 The content of PbBiO in the catalyst is low, and only PbBiO is detected in the XRD test. 2 The diffraction peak of Cl. Figure 2 As shown, the XPS characterization of Example 3 proves that Bi 2 S 3 Existing in the catalyst. Figure 3 As shown, the TEM image of Example 3 further shows that Bi 2 S 3 Nanorods adhere to PbBiO 2 Cl nanosheets. Figure 4 As shown, compared with Comparative Examples 1-2, Example 3 significantly enhances the 2 The absorption of Cl in the visible light region indirectly proves that Bi 2 S 3 At the same time, pure Bi in Example 1 2 S 3 It strongly absorbs visible light and near-infrared light and has a significant photothermal effect.

[0069] Piezoelectric catalytic degradation of RhB experiment:

[0070] (1) Prepare a 5 mg / L Rhodamine B (RhB) solution.

[0071] (2) Weigh 0.10 g of the catalysts prepared in Examples 1-5 and Comparative Examples 1-2, add 100 mL of the target degradation solution prepared in step (1) respectively, and stir magnetically for 60 minutes. After the sample materials are evenly dispersed, place the beaker in a 120 W ultrasonic cleaner for piezoelectric catalytic degradation of RhB experiment.

[0072] (3) The total duration of the piezoelectric catalytic degradation activity test was 1.5 hours. 4 mL of the reaction solution was drawn every 15 minutes. After centrifugation, the absorbance at 554 nm was measured using a UV-visible spectrophotometer. The results are as follows: Figure 5 As shown in (the blank group is the experimental group without adding any catalyst), the first-order kinetic fitting results of its degradation process are as follows Figure 6 shown.

[0073] like Figure 5 As shown, after 1.5 hours of piezoelectric catalytic degradation, the degradation effect of Examples 1-5 is significantly higher than that of Comparative Examples 1-2. Figure 6 By comparing the piezoelectric catalytic activity of Examples 1 to 5 and Comparative Examples 1 and 2, it can be observed that the degradation process of RhB conforms to the first-order reaction kinetics. The piezoelectric catalytic performance of Example 3 is the most outstanding, and its degradation rate constant is 1.95·h -1 , which is 6.7 times that of comparative example 1 and 16.2 times that of comparative example 2. Further band structure analysis shows that Bi 2 S 3 and PbBiO 2 A type I heterojunction is formed between Cl and Bi 2 S 3 By capturing PbBiO 2The electrons in Cl effectively promoted the separation of charge carriers, which was confirmed in the subsequent AC impedance analysis.

[0074] Photocatalytic degradation of RhB experiment:

[0075] (1) Prepare a 5 mg / L Rhodamine B (RhB) solution.

[0076] (2) Weigh 0.10 g of the catalyst prepared in Example 3, add 100 mL of the target degradation solution prepared in step (1), and stir magnetically for 60 minutes. After the sample material is evenly dispersed, place the beaker under a 350 W xenon lamp to carry out a photocatalytic degradation experiment of RhB.

[0077] (3) The total duration of the photocatalytic degradation activity test was 1.5 hours. Every 15 minutes, 4 mL of the reaction solution was aspirated and centrifuged. The absorbance at 554 nm was measured using a UV-visible spectrophotometer. The results are as follows: Figure 8 shown.

[0078] In the experiment, it was found that the temperature of Example 3 rose to 51° C. after 30 minutes of xenon lamp irradiation, while the temperature of Comparative Example 1 was only 31° C. under the same conditions. This temperature increase phenomenon is conducive to the activation of reactant molecules and the improvement of reaction rate.

[0079] Photo-piezoelectric synergistic catalytic degradation of RhB experiment:

[0080] (1) Prepare a 5 mg / L Rhodamine B (RhB) solution.

[0081] (2) Weigh 0.10 g of the product prepared in Example 3, add 100 mL of the target degradation solution prepared in step (1), and stir magnetically for 60 minutes. After the sample material is evenly dispersed, place the beaker in a 120 W ultrasonic cleaner and under 350 W xenon lamp light to carry out RhB catalytic degradation experiments.

[0082] (3) The total duration of the catalytic degradation activity test was 1.5 hours. Every 15 minutes, 4 mL of the reaction solution was aspirated and centrifuged. The absorbance at 554 nm was measured using a UV-visible spectrophotometer. The results were as follows: Figure 8 shown.

[0083] like Figure 8 As shown, Example 3 exhibits better photo-piezoelectric catalytic performance under the conditions of synergistic illumination and ultrasonic vibration. The piezoelectric catalytic, photocatalytic and photo-piezoelectric synergistic catalytic degradation processes of Example 3 are fitted by first-order kinetics. The results are as follows Fig. 9 As shown in Figure 3, the degradation rate constant of Example 3 under the photo-piezoelectric synergistic catalytic conditions reached 2.31·h -1 , which are 4.4 and 1.2 times that of photocatalysis and piezoelectric catalysis, respectively.

[0084] Piezoelectric catalytic degradation of RhB cycle test of Example 3:

[0085] Example 3 After a piezoelectric catalytic degradation of RhB, the catalyst was separated by centrifugation, washed three times with deionized water and anhydrous ethanol, and then dried in a 60°C oven for the next piezoelectric catalytic reaction test. This cycle was repeated six times. The results are as follows: Figure 7 shown.

[0086] like Figure 7 As shown, the catalytic activity of the catalyst prepared in Example 3 remained unchanged after six cycles of use, proving that the material has high stability.

[0087] AC impedance analysis:

[0088] Electrochemical impedance spectroscopy (EIS) analysis was performed on a CHI 660E electrochemical workstation. A standard three-electrode cell configuration was used, with the catalyst as the working electrode, Ag / AgCl (saturated KCl solution) as the reference electrode, and a platinum electrode as the counter electrode. The electrolyte used was 0.5 mol / L Na 2 SO 4 The working electrode is prepared as follows: weigh a small amount of catalyst, add appropriate amount of naphthol and ethanol, mix and grind, then coat on ITO glass and dry, the coating area is 1.0×1.0 cm. Example 3 and Comparative Example 1-2 were subjected to AC impedance analysis, and the results are as follows Fig.10 shown.

[0089] like Fig.10 As shown, compared with Comparative Examples 1-2, the catalyst prepared in Example 3 has a smaller interface resistance and a faster electron migration rate, which will prompt more electrons and holes to participate in the photo-piezoelectric catalytic reaction, and ultimately prompt the catalyst prepared in Example 3 to exhibit excellent piezoelectric catalytic and photo-piezoelectric catalytic properties.

[0090] Experiments on piezoelectric catalytic degradation of other pollutants:

[0091] (1) The concentrations of the pollutants methylene blue (MB), methylene (MO), malachite green (MG), rhodamine B (RhB), Congo red (CR), and tetracycline (TC) were all 5 mg / L.

[0092] (2) Take the Bi prepared in Example 3 2 S 3 Composite PbBiO 2 0.10 g of Cl catalyst was added to 100 mL of the target degradation solution in step (1) and magnetically stirred for 60 minutes. After the sample material was evenly dispersed, the beaker was placed in a 120 W ultrasonic cleaning machine for piezoelectric catalytic degradation of RhB.

[0093] (3) The total duration of the piezoelectric catalytic degradation activity test was 1.5 hours. Every 15 minutes, 4 mL of the reaction solution was drawn up and centrifuged before measuring its absorbance using a UV-visible spectrophotometer. The results were as follows: Fig.11 shown.

[0094] like Fig.11 As shown in Figure 3, in addition to RhB, Example 3 also exhibited excellent piezoelectric catalytic degradation capabilities for other common pollutants (methylene blue, methyl orange, malachite green, Congo red, and tetracycline). 2 S 3 Composite PbBiO 2 Cl heterojunction catalysts have great application potential in the degradation of water pollutants.

[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A catalyst of Bi2S3 composite PbBiO2Cl, characterized in that: Nano-scale Bi2S3 is deposited on PbBiO2Cl nanosheets, and the molar ratio of Bi2S3 to PbBiO2Cl in the composite catalyst is x%, wherein 1≤x≤8.

2. The catalyst of Bi2S3 composite PbBiO2Cl according to claim 1, characterized in that: The molar ratio of Bi2S3 to PbBiO2Cl is 4%.

3. The catalyst of Bi2S3 composite PbBiO2Cl according to claim 1, characterized in that: Bi2S3 and PbBiO2Cl form a type I heterojunction structure.

4. A method for preparing a catalyst of Bi2S3 composite PbBiO2Cl, characterized in that: The following steps are involved: S1 Synthesis of PbBiO2Cl: Disperse bismuth nitrate, lead acetate and sodium chloride in water and mix them evenly to form a solution; add sodium hydroxide to adjust the pH of the solution to 11; perform hydrothermal reaction at 170-185°C for 20-28h, cool to room temperature, separate the reaction solution into solid and liquid, wash and dry to obtain PbBiO2Cl; S2 deposition of Bi2S3: dispersing the obtained PbBiO2Cl in water, adding sodium sulfide and mixing evenly; adding bismuth nitrate and mixing evenly; subjecting the mixture to a hydrothermal reaction at 110-130°C for 14-18h, cooling the mixture to room temperature, separating the reaction liquid into a solid-liquid phase, washing the reaction liquid, and drying the reaction liquid to obtain a Bi2S3 composite PbBiO2Cl catalyst as described in any one of claims 1-3.

5. The method for preparing a Bi2S3 composite PbBiO2Cl catalyst according to claim 4, characterized in that: In step S1, the molar ratio of bismuth nitrate, lead acetate and sodium chloride is 1:1:

1.

6. The method for preparing a Bi2S3 composite PbBiO2Cl catalyst according to claim 5, characterized in that: In the step S1, the volume ratio of the mole of bismuth nitrate to the solution in the hydrothermal reaction is 2.9-3.1 mmol:80 mL.

7. The method for preparing a Bi2S3 composite PbBiO2Cl catalyst according to claim 4, characterized in that: In step S2, the molar ratio of sodium sulfide to bismuth nitrate is 3.5-4.5:2; and the molar ratio of PbBiO2Cl to the volume ratio of the system in the hydrothermal reaction is 1 mmol:8L.

8. An application of a catalyst of Bi2S3 composite PbBiO2Cl, characterized in that: The Bi2S3 composite PbBiO2Cl catalyst obtained by the preparation method according to any one of claims 4 to 7 is added to a liquid containing pollutants to be treated, and the pollutants are degraded by light and / or ultrasound.

9. The use of a Bi2S3 composite PbBiO2Cl catalyst according to claim 8, characterized in that: The ratio of the catalyst mass of Bi2S3 composite PbBiO2Cl to the volume of the liquid to be treated is 0.8-1.2 g / L; the power of the ultrasonic generator is 100-140W.

10. The use of a Bi2S3 composite PbBiO2Cl catalyst according to claim 9, characterized in that: The illumination uses a xenon lamp to degrade pollutants; the power of the xenon lamp is 300-400W.

Citation Information

Cited By

  • Laser power detector based on surface plasmon enhanced photo-thermoelectric effect and preparation method thereof

    CN120265094A